Respuestas

¡La mejor respuesta!
2012-09-12T08:36:14+02:00

f0=0  f1=1  f2=1  f3=2   f4=3

por demostrar

f(n-2) + f(n+2) = 3f(n)  para n>=2

 

1.-para n=2

 

f0+f4=0+3=3

3*f2=3*1=3

entonces:f0+f4=3*f2

 

2.- supongamos que cumple para n=k para n=k+1 debe cumplir

para n=k

f(k-2) + f(k+2) = 3f(k)-->f(k-2) =-f(k+2) +3f(k)---(1)


para n=k+1

f(k+1-2)+f(k+1+2)=f(k-1)+f(k+3)=f(k)-f(k-2)+f(k+1)+f(k+2)

=f(k)-(-f(k+2) +3f(k))+f(k+1)+f(k+2)   por 1

=2f(k+2)-2f(k)+f(k+1)=2(f(k+2)-f(k))+f(k+1)

=2f(k+1)+f(k+1)

=3f(k+1)

entonces:

f(k+1-2)+f(k+1+2)=3f(k+1)

cumple para n=k+1

por lo tanto

f(n-2) + f(n+2) = 3f(n)  para n>=2 es verdadero